Caracterização de curdlana produzida por Agrobacterium sp. IFO 13140 e seus géis por meio de FT-IR, FT-Raman e análises térmicas : avaliação da morfologia, propriedades físico-químicas, tecnológicas, reológicas e aplicação em alimentos - Mangolim, Camila Sampaio (2017)
Curdlan is a linear, neutral polysaccharide composed of repeated β-(1,3)-linked glucose residues, and is considered a food fiber. It is of special interest due to its gel formation properties, which allow it to be used as a gelling agent to improve the texture, water retention capacity and thermal stability of various food products. When heated, its aqueous suspension forms two types of gel: low-set gel, which is thermo-reversible and obtained by heating at temperatures between 55 and 60 °C, followed by cooling, and high-set gel, which is thermo-irreversible and obtained by heating at over 80 °C. Because of their high firmness and stability, curdlan gels are used in the manufacture of pasta, sauces, frozen and canned foods, and are biodegradable, edible and non-toxic to humans and the environment. Although curdlan is a linear polysaccharide, its conformational structure has a great influence on its dispersion and gelling properties. As the recovery of the medium and the purification of the polysaccharide can influence its conformational structure, the structural study of curdlan, as well as its physicochemical and technological properties, is essential for its more effective use in the food industry. Considering the interest in curdlan due to its dispersion, viscosity and gelling properties, the present study aimed to evaluate the structure, morphology and physical-chemical and technological properties of curdlan produced by Agrobacterium sp. IFO 13140, compared to commercial curdlan. A further objective of this study was the application of curdlan in foods, such as homemade pasta and yogurt. The strain of Agrobacterium sp. IFO 13140 acquired in lyophilized form was reactivated and added to the curdlan production medium using glucose as a carbon source. Two methodologies were used to recover the polysaccharide: pre-gelation and precipitation. In both methodologies the curdlan was solubilized with NaOH 3 mol/L solution. Subsequently it was neutralized with HCl 3 mol/L (pre-gelation) or with water (precipitation). The commercial curdlan was also subjected to the pre-gelation process and entitled pre-gelled commercial curdlan. The methodologies used to recover the curdlan were related to their functional properties. The commercial and pre-gelled commercial curdlans and the curdlan produced by Agrobacterium sp. IFO 13140 (recovered by both methods) were evaluated for their structure, morphology, physicochemical properties and dispersion and gelation capacity. After this step, the two curdlans submitted to the pre-gelation process were used for the preparation of the dispersions and gels. The mechanisms of formation of the curdlan gels were examined by FT-IR and FT-Raman spectroscopy, and their formation temperatures were evaluated by DSC and TGA analyzes. The curdlans submitted to the pre-gelation process, as well as the commercial curdlan, were evaluated for their technological properties of water absorption and oil and water solubility. Subsequently, they were applied in homemade pasta and yogurt in proportions of 1% and 1.5%, in relation to the quantities of flour and milk, respectively. The cooking characteristics and the texture profile of the pasta were evaluated. Rheology, texture and syneresis were evaluated from the yoghurt. FT-Raman analysis of the commercial and pre-gelled commercial curdlans and the curdlan produced by Agrobacterium sp. IFO 13140 (recovered by the pre-gelation and precipitation methods) revealed a structural similarity between all the samples, meaning that the curdlan produced by the microorganism has a similar structure to the commercial curdlan, and that the method used for the recovery of the polysaccharide does not influence its structure. However, scanning electron microscopy data revealed that both the drying method and the recovery method significantly affected the shape and size of the curdlan granules. The commercial (atomized) sample had large granules with concavities. The other samples (lyophilized) exhibited smaller particles. Also, the two curdlans submitted to the pre-gelation process had the smallest particle size, which may have influenced their improved dispersion in water. The results obtained in the physical-chemical analyzes revealed that the commercial curdlan had the highest carbohydrate content, followed by that produced by the microorganism and recovered by precipitation, demonstrating the greater purity of these samples. The curdlans submitted to the pre-gelation process presented a lower carbohydrate content, due to the salt incorporated in this process (calculated by the sodium content). When the characteristics of the dispersion and gelation of the curdlans were evaluated, the pre-gelled samples dispersed easily and homogenously in water, and developed a firm and homogenous gel. The commercial curdlan did not easily form a homogeneous dispersion or gel. The same was true for the curdlan produced by Agrobacterium sp. IFO 13140 recovered by precipitation, which did not gel due to the absence of sodium. Therefore, the thermal, rheological and gel strength analyzes were performed using the pre-gelled curdlans only. The commercial curdlan was compared with the pre-gelled curdlans in terms of the technological properties of absorption of water and oil and solubility in water, as well as application in foods. The FT-IR and FT-Raman analyses revealed a structural similarity between the commercial curdlan and the curdlan produced by Agrobacterium sp. IFO 13140. It was not possible to identify the structural variations resulting from the gel formation using the FT-IR technique. However, the FT-Raman technique did identify these variations, allowing variations related to the hydrogen bonding and hydrophobic interactions to be observed. The formation temperatures of both gels were determined by DSC. The samples revealed an endothermic peak between 40 and 55 °C, due to the swelling of the curdlan, and another peak between 70 and 80 °C due to hydrophobic interactions between the molecules. Additionally, rheology and gel strength analysis revealed that the curdlan produced by Agrobacterium sp. IFO 13140 had a greater thickening capacity than the pre-gelled commercial curdlan. However, the latter exhibited a greater gelling capacity, resulting in a gel with a 17% greater strength and a six times greater elastic modulus at 95 °C. This difference between the gelling properties of the curdlans is due to their different degrees of polymerization (DPn) or molecular mass, as while the commercial sample had a DPn of 334 ± 8, the sample produced by the microorganism had a DPn of 232 ± 10, corresponding to molecular masses of 54000 and 38000, respectively. When the water and oil absorption and water solubility properties of the commercial curdlan and the curdlans from the pre-gelation process were evaluated, the low water solubility and absorption of all the samples were confirmed. However, the curdlans submitted to the pre-gelation process presented high oil absorption values that were greater than those of water absorption, making these ingredients useful in the structural interactions of various foods. The use of curdlans submitted to the pre-gelation process in pasta and yoghurt improved the texture characteristics of these products. In the pasta, pre-gelled curdlans increased the cooked weight (about 10%) and significantly increased hardness, adhesiveness and gumminess. The commercial curdlan did not result in a significant improvement in any of the parameters of mass as, due to its difficulty with homogenization, it did not gel homogeneously after cooking. Similarly, when applied to the yogurt and subjected to heat treatment, the pre-gelled curdlans significantly increased the firmness and adhesiveness parameters and decreased the cohesiveness of the products, due to the structuring caused by the formation of the curdlan gel...